Reconstruction of Archives in Lithuania During the Soviet Powers Years (1918–1919) - Jegelevičius, Sigitas (Knygotyra, 1976)
The October Revolution began a new era in the archives organization – Soviet centralization of archives. His foundation was the decree of June 1, 1918 “About the reorganization and centralization of archives of the RFSSR” having a decisive influence on the organization of the archives of this time of the Soviet republics.In the measures of the Revolutionary Government of Lithuania in view of development of education and national culture a great importance has also the regulating of archives. In that way by organizing the Soviet statehood of the Lithuanian nation began also the forming of his state archives.The measures of the Soviet power in the forming of archives can be divised in three stages:1. Preparatory stage from December 1917 (the forming of the Commissariat of the Affairs of Lithuania) to December 1918 (proclamation of the Soviet power in Lithuania). During this time the commissariat collected and preserved the records evacuated from Lithuania in 1915, prepared their returning in Lithuania. There were formed the judicial foundations for their returning to Lithuania.2. This was the stage of realization of practical measures of organization of archives from December 1918 to March 13, 1919 decree. During this time was formed the Archives Commission, were preserved the most important records of Vilnius, began the forming of the state archives.3. The stage of realization of the centralization of archives beginning from the decree of March 13, 1919 to the suppression of the Soviet power in Lithuania. The Soviet Government of Lithuania was the first after the RFSSR publishing a decree about the centralization of archives. This decree was prepared taking as foundation the analogical decree of the Government of the RFSSR of June 1, 1918, but in the same time it developped the most important thesis of this document. By this decree was legalized the forming of the Central Historic Archive in Vilnius and prepared the base for the centralization of archives in Byelorussia. It was projected the composition of the state archive.The forming of archives in Lithuania was interrupted by the armed attack of the internal counter–revolution and the external intervention.